Pharmacodynamics of Linezolid Plus Fosfomycin Against Vancomycin–Resistant Enterococcus faecium in a Hollow Fiber Infection Model - Wang, Shuaishuai; Liu, Huiping; Mao, Jun; Peng, Yu; Yan, Yisong; Li, Yaowen; Zhang, Na; Jiang, Lifang; Liu, Yanyan; Li, Jiabin; Huang, Xiaohui (Frontiers in Microbiology, 2021)
The optimal therapy for severe infections caused by vancomycin-resistant Enterococcus faecium (VREfm) remains unclear, but the combination of linezolid and fosfomycin may be a good choice. The 24-h static-concentration time-kill study (SCTK) was used to preliminarily explore the pharmacodynamics of linezolid combined with fosfomycin against three clinical isolates. Subsequently, a hollow-fibre infection model (HFIM) was used for the first time to further investigate the pharmacodynamic activity of the co-administration regimen against selected isolates over 72 h. To further quantify the relationship between fosfomycin resistance and bacterial virulence in VREfm, the Galleria mellonella infection model and virulence genes expression experiments were also performed. The results of SCTK showed that the combination of linezolid and fosfomycin had additive effect on all strains; In the HFIM, the dosage regimen of linezolid (12 mg/L, steady-state concentration) combined with fosfomycin (8 g administered intravenously every 8 h as a 1h infusion) not only produced a sustained bactericidal effect of 3 4 log10 CFU/mL over 72 h, but also completely eradicated the resistant subpopulations. The expression of virulence genes was down-regulated to at least 0.222-fold in fosfomycin-resistant strains compared with baseline isolate, while survival rates of Galleria mellonella was increased (Galleria mellonella survival ≥ 45% at 72 h). For severe infections caused by VREfm, neither linezolid nor fosfomycin monotherapy regimens inhibited amplification of the resistant subpopulations, and the development of fosfomycin resistance was at the expense of the virulence of VREfm. The combination of linezolid with fosfomycin produced a sustained bactericidal effect and completely eradicated the resistant subpopulations. Linezolid plus Fosfomycin is a promising combination for therapy of severe infections caused by VREfm.